Linguistic communication of older people in the light of gerontologopaedic measures - Pawłowska-Jaroń, Halina; Siudak, Anna (Logopedia Silesiana, 2023)
Drastic demographic changes worsening in societies of developed countries necessitate the search for systemic solutions for the functioning in the elderly – economic, sociological, medical, and therapeutic solutions. In addition to the standard diagnosis of somatic lesions, it is necessary to take into account the psychological, cognitive and language disorders in patients. For years, in fact it escalates pathological aging phenomenon caused by the rising neurological incidents and neurodegenerative diseases. The authors of this study are recognising the growing problem and the reasons for this they see in the following factors: 1) low public awareness of psychophysical capabilities of the elderly results in numerous therapeutic negligence 2) the lack of standards for prophylactic, diagnostic, and therapeutic proceedings and, consequently, the minimal competence that causes aversion to helping the sick seniors.